2013
DOI: 10.1055/s-0032-1318098
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Phosphoric Acid Catalyzed Stereoselective Spiroketalizations

Abstract: The spiroketal functionality is an important structural motif present in numerous natural products. The synthesis of chiral spiroketals is typically achieved under equilibrating conditions and only few asymmetric approaches are known. We have demonstrated that chiral phosphoric acids (CPAs) could serve as effective catalysts for enantioselective spiroketalizations as well as control the course of the corresponding diastereoselective reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…2). It also should be noted that the proposed involvement of the covalently linked catalyst intermediates is consistent with the mechanistic proposals made by our group for the CPA-catalyzed reactions of acetals 27 and for the related transformation by Toste, 28 List, 29 Luo 30 and Ta-kasu 31 groups.…”
Section: Resultssupporting
confidence: 88%
“…2). It also should be noted that the proposed involvement of the covalently linked catalyst intermediates is consistent with the mechanistic proposals made by our group for the CPA-catalyzed reactions of acetals 27 and for the related transformation by Toste, 28 List, 29 Luo 30 and Ta-kasu 31 groups.…”
Section: Resultssupporting
confidence: 88%
“…Our group has a long‐standing interest in the application of chiral phosphoric acids (CPAs) to control the regio‐ and stereoselective functionalization of natural products . In our recent efforts, we demonstrated that CPAs could mimic enzymatic processes and control the regioselectivity and/or stereoselectivity of acetalization, spiroketalization, and glycosylation reactions. Inspired by the endo regiocontrol exhibited by the epoxide hydrolase Lsd19, which catalyzes the selective formation of lasalocid A rather than its kinetically favored regioisomer isolacid A (Figure B), we sought to investigate the possibility of controlling the formation of the exo and endo products through CPA catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…1,9 Readers are referred to those articles for comprehensive discussion and review of the field. Herein, we summarize our laboratory’s efforts to develop novel, stereocontrolled approaches to spiroketals, with applications in both diversity-oriented synthesis and natural product total synthesis.…”
Section: Introductionmentioning
confidence: 99%